Application of Al-Qur'an Murottal Therapy Surah Ar-Rahman in Reducing Anxiety Levels in ST-Elevation Myocardial Infarction (STEMI) Post Primary PCI Patients in ICCU Room - Luthfiyyah, Zahwah; Mutarobin, Mutarobin; Mumpuni, Mumpuni; Solihati, Indah (JENDELA NURSING JOURNAL, 2025)
Background: STEMI is the most severe form of Acute Coronary Syndrome (ACS) that occurs due to complete obstruction of the coronary artery, causing extensive myocardial ischemia and necrosis. Although Primary PCI reperfusion intervention is the main therapy and is effective in reducing mortality, many patients still experience post-operative anxiety. This anxiety can worsen cardiovascular conditions through activation of the sympathetic nervous system and HPA axis, and hinder the patient's recovery process. Therefore, non-pharmacological interventions that are appropriate to the patient's spiritual and cultural values are needed to address such anxiety. Qur'anic murottal therapy, surah Ar-Rahman, to reduce anxiety levels through the effects of relaxation and psychological calmness.Purpose: To analyze the application of murottal therapy surah Ar-Rahman to the level of anxiety of STEMI patients.Methods: Uses a case study by applying intervention for 2x in 3 days.Results: EBN intervention using statistical tests obtained an effect before and after the interventions with a p-value of 0.028, systolic BP with a p-value of 0.005, and diastolic BP with a p-value of 0.005. While HR with a p-value of 0.875.Conclusion: The application of murottal therapy surah Ar-Rahman proved effective in reducing anxiety levels and stabilizing systolic and diastolic blood pressure in patients with STEMI in the ICCU room. These results support the importance of spiritual-based non-pharmacological interventions in holistic nursing care, particularly to assist the recovery process of patients after PPCI interventions. Nurses are expected to develop competence in providing spiritual healing as part of a comprehensive nursing approach.